George Patrick Ahern papers - Ahern, George Patrick, 1859-1942.
Primarily letters exchanged between Ngan Han, chief forester of China, and Ahern as director, Philippine Bureau of Forestry, concerning the Philippine Forest School, Los Baños, the establishment of a forest school in China, and education and military training in China. Includes article entitled Restoring China's Forests, by Thomas H. Simpson, published in the March 1916 edition of Review of Reviews concerning Ahern's travels in China, his forestry career, and the reforestation movement.
Typewritten transcripts.
Collection material in English.
Army officer, conservationist, and director, Philippine Bureau of Forestry.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Han, Ngan -- Correspondence; Simpson, Thomas H; Education -- China; Forests and forestry -- China; Forests and forestry -- Philippines; Military education -- China; Army officers; Conservationists